(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current state of disorders of sex development diagnosis at Vietduc Hospital from 2015 to 2025 and analyze the advantages and challenges. Subject and methods: Cross-sectional description. Patients: all disorders of sex development patients examined at Vietduc Hospital from 2015 to 2025. Results: 99 out of 136 patients were diagnosed with disorders of sex development due to congenital adrenal hyperplasia (22 patients), 5α-reductase type 2 deficiency (25 patients), androgen insensitivity syndrome (24 patients), gonadal dysgenesis (17 patients) and Kallmann syndrome, ovotesticular syndrome (4 patients), Mayer Rokitansky Kuster Hauser syndrome (3 patients), a few patients with aplasia of the Müllerian ducts, persistent urogenital sinus. 37 patients have not had their causes identified because special diagnostic techniques, especially advanced techniques such as chromosome analysis, urinary steroid quantification, or gene mutation analysis, have not been performed. Conclusions: Viet Duc University Hospital is a pioneer in diagnosing disorders of sex development in Vietnam with many disease forms; however, many patients have not been fully diagnosed.